Case Report: Deep Cerebellar Stimulation for Tremor and Dystonia - Horisawa, Shiro; Kohara, Kotaro; Nonaka, Taku; Mochizuki, Tatsuki; Kawamata, Takakazu; Taira, Takaomi (Frontiers in Neurology, 2021)
Background: The cerebellum plays an important role in the pathogenesis and pathophysiology of movement disorders, including tremor and dystonia. To date, there have been few reports on deep cerebellar stimulation. Case Report: The patient was a 35-year-old previously healthy man with no history of movement disorders. He developed a tremor and stiffness in his left hand at the age of 27 years, which was diagnosed as a dystonic tremor. We performed right thalamotomy, which resulted in a complete resolution of the tremor; however, the dystonia persisted. Subsequently, the patient developed left foot dystonia with inversion and a newly developed tremor in the right hand and foot. The patient underwent left ventralis intermedius (VIM) deep brain stimulation (VIM-DBS) and left pallidothalamic tract DBS (PTT-DBS). Left VIM-DBS completely resolved the right hand and foot tremor, and PTT-DBS significantly improved the left hand and foot dystonia. Three months postoperatively, the patient developed an infection and wound disruption at the surgical site. We performed palliative surgery for deep cerebellar stimulation via the posterior cranial region, which was not infected. The surgery was performed under general anesthesia with the patient lying in the prone position. Eight contact DBS electrodes were used. The placement of electrodes extended from the superior cerebellar peduncle to the dentate nucleus. Both the right hand and foot tremor improved with right cerebellar stimulation. Further, both the left hand and foot dystonia improved with left cerebellar stimulation. Right and left cerebellar stimulation led to no improvement in the left hand and foot dystonia and right hand and foot tremor, respectively. Stimulation-induced complications observed in the patient included dizziness, dysphagia, and dysarthria. After the surgery, the patient developed hypersalivation and hyperhidrosis in the left side of the body, both of which did not improve with adjustments of stimulation parameters. At the 6-month follow-up, the tremor and dystonia had almost completely resolved. Conclusion: Deep cerebellar stimulation deserves consideration as a potential treatment for tremor and dystonia.